(untitled) (Iraqi Journal of Science, 2022)
Broadband satellite is playing a main role in provision global coverage and onboard processing ability over IP networks to assess user applications. In order to lower the cost, get better security, solve IPv4 addressing limitation, expand the expected advantages of modern routing and mobility characteristics; the next-generation satellite systems ought to support IPv6 and seamlessly incorporate with terrestrial networks including wireless local loops. Satellite communication links have a number of limitations compared to terrestrial communications networks such as large delay and high header overhead for IPv6 consumes the bandwidth and causes lower transmission effectiveness; however, the quality of service (QoS) (such as delay, jitter, and goodput) is adversely influenced by these demerits. Current paper proposes UDP/IPV6 header compression over Multi-Protocol Label Switch (MPLS) via satellite scheme called (MPLSHCompViaSat). The aim of the proposed scheme is to save the required bandwidth in order to provide better network utilization and consequently improves the efficiency and QoS. For the sake of performance evaluation, the proposed scheme has been tested using Network Simulator (NS2).